Peran Dinas Kebudayaan dan Pariwisata dalam Mengembangkan Pariwisata Hutan Mangrove di Desa Tanjung Batu Kecamatan Pulau Derawan Kabupaten Berau - Dedi Alfiannur; Burhanduin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
This study aims to determine the role of the Department of Culture and Tourism in developing mangrove forests in Tanjung Batu Village, Derawan Island District, Berau Regency and to determine the inhibiting factors. This type of research uses qualitative research and data collection by means of interviews, observation and documentation, while the informant technique uses a purposive sampling technique as resource persons, namely the Head of Service, staff, community or visitors. The data analysis used is an interactive model developed by Milles and Huberman. The results showed that the role of the Department of Culture and Tourism in developing mangrove forest tourism in Tanjung Batu Village, Derawan Island District, Berau Regency was quite optimal in its implementation. Tourism supporting development is carried out by increasing the quality and quantity of basic infrastructure and facilities. Promotion must be carried out so that people and tourists know about these tourist destinations. Participating in exhibitions, promotions through electronic media, internet media and promotions through tourism ambassadors. The communication system is the decision of the Tourism Office in promoting mangrove forest objects and this type of cooperation continues to be held and to build communication from various parties to decisions to be taken by the Tourism Office in promoting Mangrove Forest tourism objects. The inhibiting factors are from IT limitations and product limitations.